Protecting childhood: a children's rights approach to the interpretation of the 1951 Convention relating to the Status of Refugees - ARNOLD, SAMANTHA (Trinity College Dublin. School of Law. Discipline of Law, 2017)
This thesis explores the possibility of a children?s rights approach to the interpretation of the Refugee Convention and within that what such an approach might look like. In order to construct a children?s rights approach, the conceptualisations of children outside the legal discipline, within international children?s rights law and within refugee law and refugee discourse are analysed. This thesis analyses to what extent the Refugee Convention is capable of dealing with claims from children based on the existing conceptualisation of children which are underscored by two competing ideologies ? the child as a vulnerable object in law to be protected and the child as subject with rights and the capacity to exercise their agency.
APPROVED